2003
DOI: 10.1046/j.0022-4537.2003.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Belonging and Wanting: Meanings of Social Class Background for Women's Constructions of their College Experiences

Abstract: Data from 193 women who attended Smith College in the 1960s show that the women retrospectively represented college quite differently depending on their class background. Themes of both social segregation and academic unpreparedness were evident among the women from working-and middle-class families, while themes of a continuation of family tradition were evident among women from upper-class families. Interview data from seven women who graduated from Radcliffe in 1964 suggested that a sense of who belonged an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 9 publications
3
70
0
Order By: Relevance
“…Nonelite students often perceive themselves to be less prepared academically (Aries and Seider 2005;Stewart and Ostrove 1993) and find little in common socially with higher SES peers (Ostrove 2003). This lack or mismatch of symbolic capital is a visceral experience, memorable long into adulthood (Stewart and Ostrove 1993, as well as memoirs from formerly working class adultssee, e.g., Dews and Law 1995;Lubrano 2004;Ryan and Sackrey 1984;Tokarczyk and Fay 1993).…”
Section: The Experience Of Mobility Through Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonelite students often perceive themselves to be less prepared academically (Aries and Seider 2005;Stewart and Ostrove 1993) and find little in common socially with higher SES peers (Ostrove 2003). This lack or mismatch of symbolic capital is a visceral experience, memorable long into adulthood (Stewart and Ostrove 1993, as well as memoirs from formerly working class adultssee, e.g., Dews and Law 1995;Lubrano 2004;Ryan and Sackrey 1984;Tokarczyk and Fay 1993).…”
Section: The Experience Of Mobility Through Educationmentioning
confidence: 99%
“…Scholars of mobility have documented the inherent clash between elite and nonelite ways of being that arises during that process, typically focusing on how upwardly mobile students fare on campus (e.g., Aries 2008;Aries and Seider 2005;Goodwin 2002;Ostrove 2003;Stuber 2006Stuber , 2009Stuber , 2010Torres 2009). A corollary-students' interaction with their nonelite home communities-has received far less scholarly attention.…”
mentioning
confidence: 99%
“…Perceiving such a cue, Steele and colleagues argue, forms a working hypothesis in the individual's mind-a theory of context-that triggers a search for additional information to confirm or disconfirm the suspected potential for social identity-based devaluation. Specifically, this theory of context instigates cognitive processes (e.g., vigilance) and affective responses (e.g., anxious arousal; Murphy et al, 2007) that undermine performance on tasks that are relevant in the context (e.g., Inzlicht & Ben-Zeev, 2000, 2003Sekaquaptewa & Thompson, 2003). It is important to note that this framework is a theoretical extension of stereotype threat theory because it can account for identity-related processes beyond those associated with the threat of confirming a negative group performance stereotype.…”
Section: Social Identity Threatmentioning
confidence: 99%
“…For instance, in a retrospective study, Ostrove (2003) found that women from lower and middle-class backgrounds reported feeling more alienated or belonging less during their time spent at an elite college-echoing Walton and Cohen's (2007) work on the effects of racial underrepresentation at elite private universities. Moreover, students from lower SES backgrounds have also been found to experience concerns about their academic fit and competency in the elite university environment (Granfield, 1991).…”
Section: Ses Stigmamentioning
confidence: 99%
“…However, Jean's strongest concern is the absence of people with which she feels able to bond. Dixon and Durrheim (2004) state the notion of belonging, as a 'group response' ethnic and racial factors relating to 'our space, their space' and the concept of 'insiders and outsiders', which the student relates when describing university locations where she does not naturally fit in (Ostrove, 2003).…”
Section: Discussionmentioning
confidence: 99%